Associated plasma protein during the first trimester of pregnancy and pregnancy outcomes - Devi, Vennapusa Rama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Newborns are perhaps the most vulnerable population the world over. Preterm or babies born too early, less than 37 weeks gestation, are particularly at risk. Objective of present study were to determine the strength of relationship between PAPP-A concentrations using our own reference range and rates of idiopathic preterm delivery. Methods: A retrospective cohort study was conducted on consecutive singleton pregnancies undergoing first-trimester screening for fetal Down syndrome between 11 weeks and 14 weeks of pregnancy. Results: 500 patients in first trimester of pregnancy were selected in this study. 400 patients were found to have normal levels and were followed up till delivery. 20 patients developed preterm labour. Out of 100 patients who had low PAPP-A level, 35 patients had developed preterm labour. 15 patients out of 400 normal patients developed foetal growth retardation, 13 out of 100 low patients had foetal growth retardation. 5 out 400 normal patients developed PIH and no still birth was seen in normal patients. 15 out of 100 low patients had PIH and 2 patients had still birth. Most of the patients had asymmetrical FGR which concludes that there might be increased utero-placental resistance because of foetal growth restriction. Conclusions: In the first trimester of pregnancy, PPP-A level is an important predictor of outcome of obstetrics. A low level of PAPP-A is useful in indicating the risk of pre-term delivery and chance of PIH development.